Prevalence and Course of Idiopathic Hypersomnia in the Wisconsin Sleep Cohort Study - Plante, David T; Hagen, Erika W; Barnet, Jodi H; Mignot, Emmanuel; Peppard, Paul E (Neurology, 2024)
Idiopathic hypersomnia (IH) is a CNS disorder of hypersomnolence of unknown etiology. Due to the requirement for objective sleep testing to diagnose the disorder, there are currently no population-based estimates of the prevalence of IH nor data regarding the longitudinal course of IH in naturalistic settings. Subjective and objective data from the Wisconsin Sleep Cohort study were used to identify cases with probable IH from participants with polysomnography and multiple sleep latency test data. Demographic, polysomnographic, and symptom-level data were compared between those with and without IH. Longitudinal trajectories of daytime sleepiness among those with IH were assessed to evaluate symptom persistence or remission over time. From 792 cohort study participants with available polysomnography and multiple sleep latency test data, 12 cases with probable IH were identified resulting in an estimated prevalence of IH of 1.5% (95% CI 0.7-2.5, < 0.0001). Consistent with inclusion/exclusion criteria, cases with IH had more severe sleepiness and sleep propensity, despite similar or longer sleep times. Longitudinal data (spanning 12.1 ± 4.3 years) demonstrated a chronic course of sleepiness for most of the cases with IH, though pathologic somnolence remitted in roughly 40% of cases. These results demonstrate IH is more common in the working population than generally assumed with a prevalence on par with other common neurologic and psychiatric conditions. Further efforts to identify and diagnose those impaired by unexplained daytime somnolence may help clarify the causes of IH and the mechanisms underlying symptomatic remission.